Basic principles of the continuous casting technology development for machine‑building blanks - E. B. Demchenko; E. I. Marukovich (Литьë и металлургия, 2022)
It is shown that during developing continuous casting technology, it is necessary to solve a number of tasks related to finding the optimal technology option, creating special equipment to expand the range of cast blanks and calculating optimal parameters. The profile, dimensions and material of the blanks determine the continuous casting method choice and the installation type. Designs of the most important components and mechanisms are being developed for the selected type of installation. For the selected design solution, based on the lesson learned and available research, optimal thermal and technological parameters of casting are calculated.